Reversal of the effects of clonidine using naloxone. Issue 1 (11th March 2019) - Swift, A.; Wilson, M.
Summary: An 18‐year‐old man underwent surgery for correction of idiopathic scoliosis. Due to the requirement for intra‐operative spinal cord monitoring, propofol and remifentanil total intravenous anaesthesia was chosen as the anaesthetic technique. Clonidine was given intra‐operatively as part of his analgesic regimen. No long‐acting opioids were administered. There was delayed emergence after switching off total intravenous anaesthesia and he remained sedated with a bispectral index of approximately 60 for 90 min. The common causes of delayed emergence were excluded. Shortly after administering naloxone, there was an increase in bispectral index and emergence from anaesthesia. We describe the successful use of naloxone to reverse the sedation effects of clonidine.